Effects of concomitant selenium and vitamin E administration on thyroid hormone metabolism in broilers - PAPPAS, A. C.; KOTSAMPASI, B. M.; KALAMARAS, K.; FEGEROS, K.; ZERVAS, G.; KALOGIANNIS, D.; CHADIO, S. E. (Journal of the Hellenic Veterinary Medical Society, 2018)
A total of 400, as hatched, broilers were used to investigate the effect of selenium (Se) and vitamin E supplementation on thyroid hormones metabolism. There were 5 replicates of 4 dietary treatments namely: control (C), a soybean meal maize basal diet with adequate Se and vitamin E (0.3 mg Se per kg diet and 80 mg vitamin E per kg diet), control diet with Se added (Se+, with an additional 1 mg of Se per kg of diet), control diet with vitamin E added (E+, with an additional 350 mg of vitamin E per kg of diet) and Se+E+ (with additional 1 mg of Se and 350 mg of vitamin E per kg of diet). Diets were isonitrogenous and isocaloric. Zinc L-selenomethionine complex was used to increase Se content and dl-α-tocopheryl acetate to increase vitamin E content. The experiment lasted 42 days. Plasma Se concentration increased in Se+ groups, while whole blood glutathione peroxidase (GPx) activity increased in Se+, E+ and Se+E+ groups compared to control. Hepatic type I iodothyronine deiodinase (ID-I) and thyroid hormone concentrations were unaffected by any dietary treatment. It is concluded that supplementation with Se or vitamin Ε alone or in combination above animal’s requirements does not affect thyroid hormone metabolism and liver ID-I activity under the conditions examined.